Micromechanical modelling of alumina trihydrate filled poly (methyl methacrylate) composites. (1st January 2013) - Tarleton, E.; Charalambides, M.N.; Leppard, C.; Yeoh, J.L.
The microstructure of a binary composite consisting of stiff particles embedded in a matrix was modelled using finite element analysis. A regular square mesh was generated and an image of the microstructure was used to assign the appropriate material parameters to each integration point depending on its location relative to the original image. The same image was also used to find the particle size distribution of the filler which was used to recreate a simulated microstructure with the same volume fraction. The simulated microstructure represented the filler particles as circles with diameters ranging from 1 μm to 95 μm. The size and position of each filler particle was used to generate a model by explicitly meshing each particle boundary. The simulated microstructure reproduced the same strain values under tension as the original microstructural image, the implication being that it is possible to model a microstructure when a clear image is not available provided statistical size distribution data is available. The predicted composite modulus was compared to experimental values obtained from tensile tests available in the literature and to analytic predictions. The strain fields were compared to digital image correlation analysis of images obtained from tensile tests performed using in-situ SEM.